Ontology Specific Alternative Splicing Changes in Alzheimer’s Disease - Lu, Yanjun; Yue, Daoyuan; Xie, Jiazhao; Cheng, Liming; Wang, Xiong (Frontiers in Genetics, 2022)
Alternative splicing (AS) is a common phenomenon and correlates with aging and aging related disorders including Alzheimer’s disease (AD). We aimed to systematically characterize AS changes in the cerebral cortex of 9-month APP/PS1 mice. GSE132177 dataset was downloaded from GEO and ENA databases, aligned to GRCm39 reference genome from ENSEMBL via STAR. Alternative 3′SS (A3SS), alternative 5′SS (A5SS), skipped exon (SE), retained intron (RI), and mutually exclusive exons (MXE) AS events were evaluated using rMATS, rmats2sashimiplot, and maser. Differential genes or transcripts were analyzed using limma R package. Gene ontology analysis was performed with clusterProfiler R package. A total of 60,705 raw counts of AS were identified, and 113 significant AS events were finally selected after selection criteria: (1) average coverage >10; (2) delta percent spliced in (ΔPSI) >0.1. SE was the most abundant AS events (61.95%), and RI was the second most abundant AS types (13.27%), followed by A3SS (12.39%), then A5SS and MXE comprised 12.39%. Interestingly, genes experienced SE were enriched in histone acetyltransferase (HAT) complex, while genes spliced by RI were enriched in autophagy and those experienced A3SS were enriched in methyltransferase activity revealed by GO analysis. In conclusion, we revealed ontology specific AS changes in AD. Our analysis provides novel pathological mechanisms of AD.